EXPERIENCE IN MANAGEMENT OF ADHESIVE BOWEL OBSTRUCTION - E. Yu. D'yakonova; D. A. Morozov; S. Yu. Gorodkov; A. S. Bekin; A. Sh. Kurbanova (Вопросы современной педиатрии, 2015)
The article discusses the most common causes and strategies for treatment of adhesive bowel obstruction and its timely diagnostics (which consists in the need for X-ray, ultrasound and endoscopy). It is shown that laparoscopic adhesiolysis in conjunction with anti-adhesion therapy not only minimizes complications in the postoperative period, reduces the time of hospital stay and ensures a good cosmetic result, but also helps verify the nature and extent of adhesions, as well as exclude the presence of other abdominal cavity diseases.